Robotic Technologies in Horticulture: Analysis and Implementation Prospects (Agricultural Engineering, 2023)
The article contains an analytical review and perspectives of robotic technologies in horticulture. Trends in the growth of production, implementation, and sales of robots in various regions of the world are revealed. The analysis showed a lag in the introduction of agricultural robots compared to other sectors of the economy, as well as a significant gap between the countries of the Asian region and other continents. A review of technical means of three main components of ground agricultural robots is considered: navigation systems, sensors, and platform design. Examples of constructing a tree trajectory using the A* algorithm and using the Rviz visualization tools and the Github PathFindings graphical web service are given. As a result of the conducted research, the use of Lidar sensors is recommended, which will make it possible to design the route of robotic platforms, build maps by scanning a previously unknown surrounding space and updating the resulting map at each step of the algorithm in real time. The use of existing modern sensors with an optical rangefinder with a resolution of 4.5 million pixels, a frame rate of 25 frames per second and the ability to automatically adapt to the light level in combination with stereo cameras and GPS/GLONASS navigation will improve the positioning accuracy of robotic platforms and ensure autonomous operation. To perform basic technological operations for the care of plantings with row spacing of 2.5-4 m, a tree crown height up to 3-3.5 m with intensive technologies, the following design parameters of a robotic platform are required: agro-treatment of at least 1200 mm, adjustable track width of 1840-2080 mm, weight not more than 400 kg, load capacity not less than 1000 kg, the power of the power plant is not less than 5 kW.